2014
DOI: 10.1016/j.trc.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cooperative and autonomous adaptive cruise control dynamic responses using experimental data

Abstract: Vehicle longitudinal control systems such as (commercially available) autonomous Adaptive Cruise Control (ACC) and its more sophisticated variant Cooperative ACC (CACC) could potentially have significant impacts on traffic flow. Accurate models of the dynamic responses of both of these systems are needed to produce realistic predictions of their effects on highway capacity and traffic flow dynamics. This paper describes the development of models of both ACC and CACC control systems that are based on real exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
458
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 817 publications
(474 citation statements)
references
References 29 publications
13
458
0
3
Order By: Relevance
“…MPR is the ratio of a product or service that is being used by customers and the total estimated demand. As the CACC technology advances, we have seen an increasing amount of field experiments for CACC (Aarts and Feddes, 2016;Chang et al, 2018;Ma et al, 2019;Milans and Shladover, 2014;Xu and Peng, 2019). However, the majority of them have a limited scale and focus on the hardware aspect of the vehicle.…”
Section: Relevant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…MPR is the ratio of a product or service that is being used by customers and the total estimated demand. As the CACC technology advances, we have seen an increasing amount of field experiments for CACC (Aarts and Feddes, 2016;Chang et al, 2018;Ma et al, 2019;Milans and Shladover, 2014;Xu and Peng, 2019). However, the majority of them have a limited scale and focus on the hardware aspect of the vehicle.…”
Section: Relevant Researchmentioning
confidence: 99%
“…The conflict rate, which is derived from the vehicle interactions between AV and HV at each simulation time step, was used as a safety indicator among nine levels of CAV aggressiveness. However, the performance of each vehicle group was not separated, and the efficacy of simulating AV behavior by merely adjusting the Wiedemann model is still subject to debate (Milans and Shladover, 2014).…”
Section: Relevant Researchmentioning
confidence: 99%
“…In real-time applications, on-board sensors, for example, radar and ultrasonic, have limited perception capability, which will effect the platoon controller (5). We consider the following output characteristic of the distance sensors [19]:…”
Section: Problem Formulationmentioning
confidence: 99%
“…It is necessary to research on the behavior of these cars when interacting with existing traffic flows and with each other. The latest experiment at the California PATH showed that vehicles in platoons can maintain a time gap as small as 0.6 s, compared to 1.5 s for conventional regular vehicles, which implies a substantial increase in roadway capacity and mitigation of drastic congestion [2]. Talebpour et al examined the impacts of reserving one lane of a four-lane highway for automated vehicles on traffic flow dynamics and travel time reliability.…”
Section: Introductionmentioning
confidence: 99%